A Comparative Study of the Spatial Features of Chinese and Korean Academies: A Case Study of BaiLuDong Academy and Tosan Academy - Yirui Zhu; Kyung-Ran Choi (Buildings)
This paper presents a comparative study of the spatial characteristics of academies in China and Korea, focusing on BaiLuDong Academy in China and Tosan Academy in Korea. It examines the cultural philosophies and practical differences in the spatial expression of Confucianism between the two countries. BaiLuDong Academy embodies the Confucian ideals of simplicity and solemnity through its modest architectural style and rigorous spatial organization. The integration of mountain–water siting with enclosed courtyard arrangements reflects the Confucian scholar’s pursuit of self-cultivation and social order. In contrast, Tosan Academy, while grounded in Zhu Xi’s Neo-Confucian teachings, incorporates local architectural traditions to form a more open and flexible spatial configuration. Its emphasis on harmony with the natural environment represents a localized reinterpretation of Confucian values. As a spatial embodiment of ideology, the academy serves as a medium through which Confucian values are materialized in architectural form. The spatial characteristics of Chinese and Korean academies reveal the adaptability and evolution of Confucian thought across different cultural contexts.